Detection of archaeological crop marks in Cyprus using vegetation indices from Landsat TM/ETM+ satellite images and field spectroscopy measurements - Themistocleous, Kyriacos; Papadavid, George; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2010)
Archaeological remains can be detected using crop marks, during different periods of crop cycle. Vegetation indices and spectral signatures can be used in order to examine and evaluate such crop marks. This paper presents the methodology applied for detecting crop marks over an archaeological site of Cyprus using Landsat TM/ETM+ satellite images. Moreover the GER1500 spectro-radiometer was used to retrieve in-situ spectral signatures over the area of interest (Kouklia Village in Paphos Cyprus). The results found are characterizing very promising since crop marks were identified as spectral anomalies. This paper aims to record the phenological cycle of barley crops, over agricultural fields in which archaeological areas existed and areas where only healthy agricultural fields are presented. NDVI values from the available satellite images (Landsat TM and Landsat ETM+) are used to plot the life cycle of barley crops. For the area in which archeological crop marks were found, the NDVI plot is significantly differs from one non-stressed crop. Such area covered by barley crop has been recently excavated (summer 2010) and the excavations have verified some linear buried archaeological remains -probably houses- just 30cm below ground surface
Keywords: Archaeological crop mark; Landsat; Cyprus; NDVI; Spectral signature